CHRONIC MAXILLARY SINUSITIS – DIAGNOSIS AND ENDOSCOPIC MANAGEMENT - HAMID ABDUL QAIYUM,; UROOJ AHMED CHOUDHRY, (International Journal of Pharma and Bio Sciences, 2015)
Sinusitis is a common condition. Women are more often affected than men. Chronic sinusitis affects approximately 12.5% of people. Treatment of sinusitis in the United States results in more than 11 billion USD in costs. Although much has been written about the surgical technique of functional endoscopic sinus surgery (FESS), little has appeared about its long-term results.In the present study out of 42 patients 26 underwent bilateral surgeries and 16 underwent unilateral surgeries. 26 procedures of polypectomy were done. Apart from that 6 underwent septoplasty. Sphenoidotomy was done in 3 patients. Uncinectomy & MMA was done in all cases. Total ethmoidectomy was done in 10 patients, &conchoplasty was done in 7 patients. The present study validated endoscopic sinus surgery as it showed that the procedure resulted in an improvement in patient general and physical health.